One or two pups - optimal reproduction strategies of common noctule females - Katerina Zukalova; Veronika Seidlova; Vladimir Piacek; Monika Nemcova; Michal Pribyl; Jiri Pikula; Jan Zukal (BMC Zoology, 2022)
Abstract Background The success of animal reproduction is impacted by a trade-off between energetic costs and mortality associated with immediate vs. future reproductive attempts. The reproductive strategies of European insectivorous bats differ from common mammalian standards due to the use of delayed fertilisation. Phenology of bat reproduction, including length of pregnancy, which may vary in the same species at different latitudes, between years at the same site or between individuals within a colony, is influenced by ecological conditions. To assess factors influencing the course of pregnancy, we evaluated levels of blood progesterone in 20 female common noctule bats Nyctalus noctula. The bats were individually tagged and randomly divided into two groups with different hibernation ending points (i.e. a control group vs. a treatment group with one-week longer hibernation). Following emergence from hibernation, the bats were kept in a wooden box at a stable temperature of 22 °C. Results The majority of females gave birth to a single neonate (65%), but one female aborted her pups 2 days before the first successful births of other females. Based on development of progesterone concentration, we were able to define a number of different reproduction strategies, i.e. females with single offspring or twins, and females with supposed resorption of one embryo (embryonic mortality after implantation of the developing fertilised egg). Progesterone levels were much higher in females with two embryos during the first part of gestation and after birth. Progesterone levels were at their highest mid-gestation, with no difference between females carrying one or two foetuses. Length of gestation differed significantly between the two groups, with the longer hibernation (treatment) group having a roughly two-day shorter gestation period. Conclusions Female N. noctula are able to manipulate their litter size to balance immediate and future reproduction success. The estimated gestation length of approx. 49-days appears to be standard for N. noctula, with females optimising their thermoregulatory behaviour to keep the length of gestation as close to the standard as possible.